ANALISIS TENTANG SIKAP MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU TERHADAP PELAKSANAAN PILKADA LANGSUNG DAN TIDAK LANGSUNG DI INDONESIA - Nur Supiati; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: discourse to change the Election Law which has authority to elect regional heads returned to Parliament, which means that the implementation of the election is no longer directly, but through representatives who sit in the legislature region. Many opinions arise when the Draft Law on Election by Parliament was published to the public either in the form of acceptance or rejection. As intellectuals, students should be able to read the situation and assess appropriately supported all the knowledge to determine the correct attitude towards a political problem that occurred at that time and be a good example for society. Formulation of the problem in this research is how the attitude of Pancasila and Citizenship Education students of the Faculty of Education, University of Riau on the implementation of Direct Indirect election in Indonesia. This study aims to determine the attitude of Pancasila and Citizenship Education students of the Faculty of Education, University of Riau on the implementation of Direct and Indirect elections in Indonesia. That is the subject in this study were all students of Pancasila and Citizenship Education, the Faculty of Education, University of Riau from 2011-2014 workforce numbering 245 persons and a sample of 152 people. In setting the sample using a sampling technique Slovin is with precision of 5% from 245 students to 152 students. Data gathered through questionnaires, and technical literature. In analyzing the data using qualitative descriptive technique with percentages.The results showed that the number of respondents who answered "agree" to the implementation of direct elections as much as 62.98% in the range of 33.33% -66.67% means that the respondents are approved the implementation of direct elections in Indonesia. As for the elections Indirect respondents who answered "agree" as much as 66.08% is also in the range of 33.33% - 66.67%, the respondents are approved implementation Indirect elections in Indonesia. Keywords: Attitudes, elections Direct, Indirect elections.